Subversive legal history: a manifesto for the future of legal education: by Russell Sandberg, Routledge, 2021, 242 pp., £120 (hardback), £33.29 (ebook), Abingdon (hardback), ISBN 9780367191290 (ebook), ISBN 9780429200618. Issue 4 (2nd October 2022) - Rutherford, Helen
ABSTRACT: Legal academics and legal education are not noted for their punk aesthetic. In Subversive Legal History: A Manifesto for the Future of Legal Education Professor Russell Sandberg urges law schools to be brave and asserts that future legal education would be well served by calling legal history in aid and placing it at the centre of curriculum planning. He makes the case for legal history to come out of the shadows and take its rightful place as the disruptor of the standard law school approach to legal education, in short, to subvert the norm and form the foundation for all legal education.